2015
DOI: 10.5194/amt-8-671-2015
|View full text |Cite
|
Sign up to set email alerts
|

Towards the retrieval of tropospheric ozone with the Ozone Monitoring Instrument (OMI)

Abstract: Abstract.We have assessed the sensitivity of the operational Ozone Monitoring Instrument (OMI) ozone profile retrieval algorithm to a number of a priori and radiative transfer assumptions. We studied the effect of stray light correction, surface albedo assumptions and a priori ozone profiles on the retrieved ozone profile. Then, we studied how to modify the algorithm to improve the retrieval of tropospheric ozone. We found that stray light corrections have a significant effect on the retrieved ozone profile bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Temperature-dependent ozone absorption in the Huggins bands adds additional tropospheric ozone information (Chance et al, 1991). Based on these principles, two ozone profile algorithms were implemented: the operational algorithm (OMO3PR) at KNMI (Kroon et al, 2011;Mielonen et al, 2015) and the research algorithm (PROFOZ) at the US Smithsonian Astrophysical Observatory (SAO; Liu et al, 2010a, b;Kim et al, 2013). Both retrieve ozone profiles from the spectral region 270-330 nm using the optimal estimation method, but they differ significantly in implementation details including radiometric calibration, radiative transfer model simulation, a priori constraint, retrieval grids, and retrieval parameters.…”
Section: Profile Retrieval Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature-dependent ozone absorption in the Huggins bands adds additional tropospheric ozone information (Chance et al, 1991). Based on these principles, two ozone profile algorithms were implemented: the operational algorithm (OMO3PR) at KNMI (Kroon et al, 2011;Mielonen et al, 2015) and the research algorithm (PROFOZ) at the US Smithsonian Astrophysical Observatory (SAO; Liu et al, 2010a, b;Kim et al, 2013). Both retrieve ozone profiles from the spectral region 270-330 nm using the optimal estimation method, but they differ significantly in implementation details including radiometric calibration, radiative transfer model simulation, a priori constraint, retrieval grids, and retrieval parameters.…”
Section: Profile Retrieval Algorithmsmentioning
confidence: 99%
“…Typically, the retrievals have 5-7 degrees of freedom (DOF) for signals of ozone with up to ∼ 1.5 DOF in the troposphere. It has been shown that tropospheric ozone column can be directly and accurately retrieved in the few Dobson units range from OMI data alone on the spatial pixelto-pixel basis, but successful retrievals of tropospheric ozone and further capture of tropospheric ozone trends require accurate forward model simulation, well-characterized prior information, and consistently accurate radiometric calibration over the entire record (Liu et al, 2010a, b;Mielonen et al, 2015).…”
Section: Profile Retrieval Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done by adjusting the amount of ozone in 18 atmospheric layers. However, there must be prior knowledge of ozone profiles as well as other parameters such as surface albedo for the retrieval to be constrained (Mielonen et al, 2015). Ten years of data are used for this study, i.e.…”
Section: Ozone Monitoring Instrument (Omi)mentioning
confidence: 99%
“…Temperature-dependent ozone absorption in the Huggins bands adds additional tropospheric ozone information (Chance et al, 1997). Based on these principles, two ozone profile algorithms were implemented: the operational algorithm (OMO3PR) at KNMI (Kroon et al, 2011;Mielonen et al, 2015) and the research algorithm (PROFOZ) at the US Smithsonian Astrophysical Observatory (SAO) (Liu et al 2010a, b;Kim et 20 al., 2013). Both retrieve ozone profiles from the spectral region 270-330 nm using the optimal estimation method, but they differ significantly in implementation details including radiometric calibration, radiative transfer model simulation, a priori well-characterized prior information, and consistently accurate radiometric calibration over the entire record (Liu et al, 5 2010a(Liu et al, 5 , 2010bMielonen et al, 2015).…”
Section: Profile Retrieval Algorithmsmentioning
confidence: 99%